Desain Tata Kelola Teknologi Informasi Hotel Menerapkan Kerangka COBIT 2019 - Joe Yuan Mambu; Rinny Rantung; Stenly Adam; Debby Pungus (STMIK Budi Darma, 2023)
The advancement of technology has ushered the world into a new era, particularly in the field of information. In this context, information technology plays a significant role in supporting and enhancing the management of companies to remain competitive. One commonly used method in managing information technology is IT governance, which is included in the framework of COBIT (Control Objective for Information and Related Technology) 2019. Until now, there has been no evaluation or research conducted on the IT performance of Hotel Sutan Raja, thus the extent of the implementation of information technology in the hotel's operations is still unknown. This project focuses on the use of information systems and IT at Hotel Sutan Raja to manage the hotel's operations and data. The project was carried out by conducting a literature study on the design factors of COBIT 2019, with the result that there are four core models with high levels of importance for the Hotel Sutan Raja governance system, namely APO06, DSS01, EDM04, and BAI07. Five core models are at level 2, while two core models are at level 1